The Relationship Leadership Style, Stress and Work Motivation with Organizational Commitment of Teachers of Children with Special Needs in Special Schools in Jambi Province - Ridwan Ridwan; Mukhtar Latif; Risnita Risnita (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
organizational commitment of teachers of children with special needs in special schools, both partially and simultaneously. This research is quantitative research using a survey method carried out at State Special Schools in Jambi Province. The population is 106 people and the sample uses random sampling. The hypothesis in this research is: leadership, stress, work motivation and organizational commitment of teachers of children with special needs have a significant relationship, both partially and simultaneously, to Teacher Organizational Commitment. Hypothesis testing uses Pearson Product Moment Correlation technique analysis and multiple regression, with an alpha significance level of 5 percent (α=0.05). This research produced findings in detail, there is a direct relationship between leadership style (X1), stress (X2), and work motivation (X3) with organizational commitment Teacher of Children with Special Needs. Based on the results of analytical calculations, the calculated t value was obtained (29.065). >t table (2.68), so H0 is rejected and H1 is accepted. Leadership style, stress and work motivation have a significant relationship with the organizational commitment of teachers of children with special needs. Based on the research findings, it can be concluded that the variables of leadership style, stress and work motivation make a significant contribution to the organizational commitment of teachers of children with special needs.